2017
DOI: 10.1373/jalm.2017.023762
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Laboratory Practices to Reduce Specimen Labeling Errors at the Time of Specimen Collection in Healthcare Settings: A Laboratory Medicine Best Practices (LMBP) Systematic Review

Abstract: Background Specimen labeling errors have long plagued the laboratory industry putting patients at risk of transfusion-related death, medication errors, misdiagnosis, and patient mismanagement. Many interventions have been implemented and deemed to be effective in reducing sample error rates. The objective of this review was to identify and evaluate the effectiveness of laboratory practices/ interventions to develop evidence based recommendations for the best laboratory practices to reduce labeling errors. Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 29 publications
1
15
0
Order By: Relevance
“…Unique patient identification is an integral part of healthcare service delivery. Correctly identifying patients is critical when undergoing clinical procedures, reporting of test and procedure results, as well as managing administrative functions such as scheduling and billing [1][2][3]. Unique identification of individuals is essential in case-based disease surveillance.…”
Section: Introductionmentioning
confidence: 99%
“…Unique patient identification is an integral part of healthcare service delivery. Correctly identifying patients is critical when undergoing clinical procedures, reporting of test and procedure results, as well as managing administrative functions such as scheduling and billing [1][2][3]. Unique identification of individuals is essential in case-based disease surveillance.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of solutions to this problem have been proposed ranging from procedural [ 7 ] and wrist band information [ 7 ] changes to bedside checks [ 15 ], real-time audits [ 16 ], training changes [ 17 ], and increasing “communication and collaboration” between providers and laboratory staff [ 18 ]. Technological solutions such as improved wristband technologies [ 19 ], the use of neural network image processing to identify patient sex to identify and reduce errors [ 20 ], using RFID and wireless technologies [ 21 ] and “proximity-based medical record retrieval” [ 22 ] have been proposed.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9] In addition, manual processes are susceptible to specimen contamination, labeling error, and variability in culture quality. 10,11 To address these and other common problems encountered in the clinical laboratory, automation can be employed to streamline and standardize laboratory workflows. Several studies have shown improved laboratory workflow efficiency, 3-5, 10, 12-16 result reproducibility, 4,5,13,[15][16][17][18][19] and decreased incidence of errors 10,13,[18][19][20][21] following the implementation of automation-related processes.…”
Section: Introductionmentioning
confidence: 99%